An Up-scalable, Infiltration-Based Approach for Improving the Durability of Ni/YSZ Electrodes for Solid Oxide Cells. Issue 2 (5th February 2020) - Tong, Xiaofeng; Hendriksen, Peter Vang; Hauch, Anne; Sun, Xiufu; Chen, Ming
Abstract : In solid oxide electrolysis cells (SOECs), considerable degradation of the Ni/YSZ electrode during long-term electrolysis operation at high current densities (−1 A cm −2 or above) has been an ongoing challenge. In this work we report on a method alleviating the problem based on infiltrating nano-sized electrocatalysts into the Ni/YSZ electrode of a full cell after it has been reduced in a "one-atmosphere-reduction" process. The performance and durability of infiltrated and non-infiltrated cells are evaluated at full test-cell size of 4 × 4 cm 2 level. The infiltrated cell exhibits significantly enhanced durability when operated for steam electrolysis at 750 °C under high current densities, with cell voltage degradation rates of 0.028 V kh −1 (2.0% kh −1 ) for 800 h at −1.25 A cm −2 and 0.010 V kh −1 (0.8% kh −1 ) for 300 h at −1.00 A cm −2 . These degradation rates are ∼14 times and ∼25 times smaller than those of the non-infiltrated cell, respectively. The infiltrated cell also shows superior durability to the non-infiltrated cell during reversible operation. These results demonstrate the great potential of boosting the durability of state-of-the-art Ni/YSZ fuel electrodes for electrolysis operation via this infiltration-based approach.